2015
DOI: 10.1037/pas0000126
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk screening: Comparing the Beck Depression Inventory-II, Beck Hopelessness Scale, and Psychache Scale in undergraduates.

Abstract: The current research evaluates the effectiveness and relative merits of 3 screening measures (the Beck Depression Inventory-II, the Beck Hopelessness Scale, and the Psychache Scale) in evaluating preexisting suicide risk factors for a sample of 7,522 undergraduate students. All measures demonstrated significant diagnostic accuracy for indicating suicide ideation, previous single and multiple suicide attempts, and a recent suicide attempt, which are all serious risk factors for subsequent death by suicide in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
2
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 33 publications
2
51
2
7
Order By: Relevance
“…With average psychological pain scores in the low thirties, our sample experienced a higher level of psychological pain than was observed in a large sample of undergraduate students (20.35 [SD 8.25] Troister, D’Agata & Holden, 2015). As expected, our observed scores were higher than those found previously in healthy adults (13.70 [SD 0.50] Cáceda et al, 2014) and (20.60 [SD 4.95] Xie et al, 2014), and not quite as high as the level of psychological pain observed in outpatients with major depressive episodes (40.01 [SD 11.86] Li et al, 2014).…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…With average psychological pain scores in the low thirties, our sample experienced a higher level of psychological pain than was observed in a large sample of undergraduate students (20.35 [SD 8.25] Troister, D’Agata & Holden, 2015). As expected, our observed scores were higher than those found previously in healthy adults (13.70 [SD 0.50] Cáceda et al, 2014) and (20.60 [SD 4.95] Xie et al, 2014), and not quite as high as the level of psychological pain observed in outpatients with major depressive episodes (40.01 [SD 11.86] Li et al, 2014).…”
Section: Discussioncontrasting
confidence: 51%
“…This implies 13% fewer false positives when screening for suicide ideation among general population adults with the PS-TF. In a comparable analysis of undergraduate students with suicide ideation, Troister, D’Agata & Holden (2015) reported a specificity of .79 and PPV of .27 when using the PS. These values are respectively 2% points and 21% points lower than obtained with the PS-TF.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations